Correlation of body mass index on waist circumference and blood pressure - Yoni Astuti; Ikhlas Muhammad Jenie (International Journal of Public Health Science (IJPHS), 2020)
The increasing number of elderly on these recent days demands an improved quality of health for the elderly. Independence of the elderly is important in order to be happy and not to be a burden on their families. Health monitoring continuously is an effort to prevent disruption on the health conditions of the elderly. The health status of elderly people is important to know to follow up on prevention programs for the emergence of certain diseases in the elderly. This study aims to look for potential health problems for elderly people in Gamping, Sleman, DIY, Indonesia. The method of this research was cross sectional analysis using secondary data. Sample collection is consecutive subjects. Subjects were 158 people with a mean age of men (67.8 ± 7.1) years while women were 67.5 ± 7.3 years. The data was analyzed using the bivariate correlation test with CI 99%. The results of the analysis showed that the average body mass index with an average waist circumference was positively correlated (r= 0.66; p: 0.000), but did not correlate with systole pressure (r= -0.009; p= 0.97) diastole (r= 0.093; p= 0.477), age (-0.05; p= 0.71), and gender (r= -0.146; p= 0. 27). The potential health problems among the elderly is the risk of high BMI due to the larger waist circumference